INTERPRETASI MAKNA LIRIK LAGU-LAGU GRUP MUSIK ERK DALAM ALBUM ERK: Kajian Semiotika - Rendi Patria; Abdurahman Abdurahman; Bakhtaruddin Nasution (Jurnal Bahasa dan Sastra, 2013)
The purposes of this research were to describe  and explain (1) the meaning of Efek Rumah Kaca’s (ERK) songs lyrics in ERK’s album based on semiotic reading, (2) matrix and model of ERK’s songs lyrics in ERK’s album, (3) intertekstuality of ERK’s songs lyrics in ERK’s album. The data of research are taken from twelve songs of ERK in the ERK album . Data were collected by listening and transcript the song. The result of research were (1) based on semiotic reading the ERK’s songs lyrics in ERK’s album raise complex social issues, (2) the determination of the matrix and the integrity of the model greatly help unravel the meaning of the ERK’s songs lyrics in ERK’s album, and (3) interktekstuality ERK’s songs lyrics in ERK’s album found in the Quranic verse, film, poetry, and social realities in society.